2019
DOI: 10.1002/smll.201900520
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Dynamics of 1D Materials: Gas‐Phase Collision Rates of Nanotubes and Nanorods

Abstract: The agglomeration and self‐assembly of gas‐phase 1D materials in anthropogenic and natural systems dictate their resulting nanoscale morphology, multiscale hierarchy, and ultimate macroscale properties. Brownian motion induces collisions, upon which 1D materials often restructure to form bundles and can lead to aerogels. Herein, the first results of collision rates for 1D nanomaterials undergoing thermal transport are presented. The Langevin dynamic simulations of nanotube rotation and translation demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…In process C1, a stable aerosol bubble is blown while process C2 transforms the bubble from an aerosol into an aerogel. The SWCNTs in C1 aerosol have some interaction, [ 11,13 ] which is different in the general aerosol, [ 14 ] and could be transformed under a suitable condition into SWCNT aerogel in C2 as a final product. [ 13,15 ] BACVD essentially combines a blowing SWCNT‐aerosol technique with FCCVD for CNT synthesis.…”
Section: Figurementioning
confidence: 99%
“…In process C1, a stable aerosol bubble is blown while process C2 transforms the bubble from an aerosol into an aerogel. The SWCNTs in C1 aerosol have some interaction, [ 11,13 ] which is different in the general aerosol, [ 14 ] and could be transformed under a suitable condition into SWCNT aerogel in C2 as a final product. [ 13,15 ] BACVD essentially combines a blowing SWCNT‐aerosol technique with FCCVD for CNT synthesis.…”
Section: Figurementioning
confidence: 99%
“…It is experimentally observed that these bundles consist of about 3-20 close-packed CNTs and may be considerably longer than the individual CNTs. 5 Subsequently, the bundles collide and entangle to form a network of bundles, which is then drawn out of the furnace as fibre spun on a rotating drum, or as CNT sheets. The process of a dilute CNT aerosol to gel transition is referred to as a CNT aerogel in line with work for gas-phase spherical aggregates 6 and colloidal sol-gel systems.…”
Section: Na No Tu Be Gr Ow Th On Ca Ta Lys T Pa Rti Cle Smentioning
confidence: 99%
“…However, CNTs form bundles, due to weak van der Waals interactions, which exhibit higher stiffness and have a greater cross‐sectional area compared to individual CNTs. [ 49 ] Furthermore, multi‐walled CNTs (MWCNTs) are also known to be stiffer compared to SWCNTs. [ 50 ] The higher stiffness and effective cross‐sectional area of these structures may significantly lower the necessary electric field strength for alignment.…”
Section: Application To Alignment Of Carbon Nanotubes In An Electric Fieldmentioning
confidence: 99%